Study of dijet events with large rapidity separation in proton-proton collisions at root s=2.76 TeV - CMS Collaboration; Damarseçkin, Serdal (SPRINGER, 2022)
The cross sections for inclusive and Mueller-Navelet dijet production are measured as a function of the rapidity separation between the jets in proton-proton collisions at √ s = 2.76 TeV for jets with transverse momentum pT > 35 GeV and rapidity |y| < 4.7. Various dijet production cross section ratios are also measured. A veto on additional jets with pT > 20 GeV is introduced to improve the sensitivity to the effects of the BalitskyFadin-Kuraev-Lipatov (BFKL) evolution. The measurement is compared with the predictions of various Monte Carlo models based on leading-order and next-to-leading-order calculations including the Dokshitzer-Gribov-Lipatov-Altarelli-Parisi leading-logarithm (LL) parton shower as well as the LL BFKL resummation.
Keywords: Hadron-Hadron Scattering; Jet Physics